Students’ Online Learning Satisfaction in Relation to their Academic Performance in Mathematics - Katherine Rose G. Lopez; Jhed Gabriel L. Sanchez; Vincent Cataraja; Genelyn Baluyos (PT ARRUS Intelektual Indonesia, 2024)
Students' satisfaction are indicator of academic success in relation to the student's performance in online learning. This study determined the predictors of students' academic performance at Misamis University, particularly Junior High School students. The total populations of junior high students were 415, and the target respondents were 200 students. The researchers used the descriptive-correlational research design and the Students' Online Learning Satisfaction Questionnaire (SOLSQ) as instruments. Mean, standard deviation, Pearson r, and Stepwise Regression Analysis were the statistical tools used. Findings revealed that students were highly satisfied with their online learning. They performed very satisfactorily in their online class. There was a significant relationship between the students’ online learning satisfaction and their academic performance in mathematics. Teacher characteristics predicted students' academic performance in Mathematics. Knowledge and literacy in using technologies as a medium for instruction help teachers to be more effective in teaching online learning. The study recommends that teachers need to be digitally literate in using technology as a medium of instruction. Future researchers have to look into other factors that might contribute to the student's academic performance in online learning.